1992
DOI: 10.1042/bj2840761
|View full text |Cite
|
Sign up to set email alerts
|

Effect of treatment in vivo of rats with bacterial endotoxin on fructose 2,6-bisphosphate metabolism and L-pyruvate kinase activity and flux in isolated liver cells

Abstract: The effect of treatment of rats with bacterial endotoxin on fructose 2,6-bisphosphate (Fru-2,6-P2) metabolism was investigated in isolated liver cells prepared from 18 h-starved animals. The results obtained support the hypothesis that a stimulation of 6-phosphofructo-1-kinase (PFK-1) activity and an inhibition of fructose-1,6-bisphosphatase (Fru-1,6-P2ase) may be one mechanism underlying the inhibition of gluconeogenesis from lactate and pyruvate by endotoxin. We suggest that the stimulation of PFK-1 and inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
36
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(46 citation statements)
references
References 32 publications
10
36
0
Order By: Relevance
“…It was suggested that the major defect is the result of an activation of 6-phosphofructo-l-kinase, the resultant increase in Fru-1 ,6-P2 feeding back and activating pyruvate kinase, thus diminishing the conversion of PEP into glucose. Further studies have confirmed that a major effect of endotoxin Volume 23 is to increase flux through 6-phosphofructo-1-kinase by 3-4-fold and that this effect is independent of the presence of glucagon or glucose [7].…”
Section: Site Of Action Of Endotoxinmentioning
confidence: 87%
See 1 more Smart Citation
“…It was suggested that the major defect is the result of an activation of 6-phosphofructo-l-kinase, the resultant increase in Fru-1 ,6-P2 feeding back and activating pyruvate kinase, thus diminishing the conversion of PEP into glucose. Further studies have confirmed that a major effect of endotoxin Volume 23 is to increase flux through 6-phosphofructo-1-kinase by 3-4-fold and that this effect is independent of the presence of glucagon or glucose [7].…”
Section: Site Of Action Of Endotoxinmentioning
confidence: 87%
“…T h e activation of 6-phosphofructo-1-kinase correlates with changes in the concentration of fructose-2,6-bisphosphate (Fru-2,6-P2) in both hepatocytes [7] and freeze-clamped livers [9]. A number of reports in the literature have suggested that treatment of the animal with LPS results in increased hepatic concentrations of hexose phosphates [9,10], which could lead to an activation of 6-phosphofructo-2-kinase and inhibition of fructose-2,6-bisphosphatase (Fru-2,6-Pzase) activity, and therefore an elevation of Fru-2,6-P2.…”
Section: Site Of Action Of Endotoxinmentioning
confidence: 99%
“…These results differ slightly from the observations of others that have used much higher doses of LPS to suppress gluconeogenesis and showed increases in glycolytic genes such as Phosphofructokinase-1 and decreases in gluconeogenesis genes Fructose 2, 6 bisphosphate, Phosphoenolpyruvate carboxy kinase, and Glucose 6 phosphate. [21, 22, 42, 43]. Our studies showed decreases in glycolytic and gluconeogenic genes with no change in Pepck .…”
Section: Discussionmentioning
confidence: 52%
“…Much less is known about whether the short-term low-magnitude changes in endotoxin levels following a meal are capable of causing an inflammatory response and what role an inflammatory response would have on glucose metabolism. Previous studies aimed at determining the effects of short term endotoxin treatments on glucose metabolism have shown severe hypoglycemia, due in large part to increased glucose uptake along with inhibition of hepatic glucose production [2124]. These studies used extremely high doses of endotoxin (4–5mg/kg), many at septicemic levels.…”
Section: Introductionmentioning
confidence: 99%
“…In agreement, the stressed uninfected group suffered depletion of hepatic glycogen depots and succeeded in maintaining glucose supply in the blood. However, infectedstressed and infected food-deprived rats showed depletion of glycogen stores and failure of hepatic gluconeogenesis to maintain glucose concentrations, as in septic (Ceppi et al 1992) or endotoxic shock syndrome (Knowles et al 1987). Changes observed in vivo are not exclusively due to regulatory hormones as inflammatory cytokines may have direct effects on hepatocytes, so reducing liver capacity to synthesize glycogen (Flores et al 1990;Wallington et al 2008).…”
Section: Discussionmentioning
confidence: 94%